Current Quantum Optics Research: Exploring the Potential of Quantum Computing - McCarty Elliot; Scherschligt Oscar; Morse Kathryn (Yayasan Adra Karima Hubbi, 2024)
Quantum Optics is a branch of physics that studies the interaction between light and matter on a quantum scale. Research in this field aims to understand the basic properties of light particles (photons) and matter (atoms, molecules) and utilize them in various applications, including quantum computing. The aim of this research is to explore the potential of quantum computing in the context of Quantum Optics. This includes quantum algorithm development, experimental implementation, and practical applications in quantum information processing. The research method used involves a combination of theoretical and experimental approaches. The theoretical approach involves the development and mathematical analysis of Quantum Optics models, while the experimental approach involves the design and implementation of quantum physics systems in the laboratory. The research results show significant progress in the development of quantum algorithms that can be used in modeling quantum physics systems, quantum information processing, and other applications. In addition, the experimental results also show achievements in the implementation of quantum system prototypes that can be applied in the field of quantum computing. From the research that has been conducted, it can be concluded that quantum computing has great potential in improving the understanding of quantum physical systems and in developing new technologies based on quantum principles. However, challenges such as quantum quality control and maintenance and system scalability remain the focus of future research. As such, current Quantum Optics research offers exciting and potentially paradigm-shifting insights into future information processing and computing technologies